Hydatidiform Mole in Ectopic Pregnancy Clinical, Imaging, Pathological and Immunohistochemical Characteristics - Cortes-Charry, Rafael; Salazar, Aleydah; Garcia-Barriola, Victoria; Dabed, Pablo; Figueira, Lina M.; Maestá, Izildinha [UNESP] (Sci Printers & Publ Inc, 2012)
OBJECTIVE: To determine the clinical, pathological, immunohistochemical and imaging characteristics of hydatidiform mole in ectopic pregnancy (HMEP) in all the cases admitted to the Department of Obstetrics and Gynecology, University Hospital of Caracas (HUC), Central University of Venezuela.STUDY DESIGN: Retrospective and comparative study, based on clinical records review of 2 groups: 10 cases with a diagnosis of HMEP and 20 cases with intrauterine hydatidiform mole (IUHM) admitted to the Obstetrics and Gynecology Department of HUC from 1996 to 2010. Clinical, pathological, immunohistochemical and imaging features were analyzed.RESULTS: The prevalence of HMEP in this study was 0.14:1,000 pregnancies; in this group the mean age was 28.8 years, and the mean gestational age at admission was 8.6 weeks. Both groups (HMEP and IUHM) were comparable in these last variables. Abdominal pain and genital bleeding were the most common clinical symptoms in the HMEP group, while it was vaginal bleeding in the IUHM group. Ultrasound findings were similar to those traditionally described in nonmolar ectopic pregnancy. Histology and immunohistochemistry showed that all cases of HMEP were partial mole.CONCLUSION: Although in this study the prevalence of HMEP was high, the size of the sample limits definitive conclusions. This study concludes that all cases of HMEP are partial mole. (J Reprod Med 2012;57:329-332)
Keywords: ectopic pregnancy; hydatidiform mole; hydatidiform mole, partial